Moderate exercise improves semen quality by enhancing antioxidant and micronutrient levels in obese men - Alaa Sajid Shukur; Nihad Nejres Hilal (Middle East Fertility Society Journal)
Abstract Context Amid the silent epidemic of male infertility, obesity has emerged as a leading antagonist—fueling oxidative stress, disrupting hormonal balance, and impairing sperm function. Male reproductive health is increasingly recognized as a reflection of overall metabolic and endocrine function, and obesity-related infertility has become a growing public health concern. Identifying effective, non-pharmacological interventions that target underlying oxidative stress is essential in improving reproductive outcomes. Aims This study investigates whether a non-invasive, lifestyle-based remedy—moderate-intensity exercise—can reshape this narrative by restoring antioxidant capacity and improving semen quality in obese men. Methods The case–control research included 90 obese individuals (BMI 30–35 kg/m2; age 20–40). The participants were divided into an exercise group (n = 60) and a sedentary control group (n = 30). The exercise group had engaged in moderate-intensity physical activity for a minimum of 12 weeks prior to the start of the trial, whereas the sedentary control group had not participated in regular exercise. Biochemical profiling assessed serum levels of CoQ10, GSH, and vitamin D. Semen parameters, including volume, count, motility, and morphology, were also evaluated after 12 weeks of structured moderate-intensity physical activity. Results Biochemical profiling revealed significant elevations in serum CoQ10 (p = 0.04), GSH (p = 0.006), and vitamin D (p = 0.009) following exercise intervention. These changes were mirrored by substantial enhancements in semen volume, sperm count, motility, and morphology (all p < 0.05). Antioxidant levels were positively correlated with sperm quality metrics. Conclusion These findings demonstrate the clinically relevant potential of exercise as a low-cost, accessible, and scientifically plausible lifestyle strategy to counteract obesity-driven male infertility, offering a promising, non-pharmacological pathway for fertility improvement.